TEACHER QUESTIONING IN CLASSROOM INTERACTION - Sarlita Dewi Matra (Soegijapranata Catholic University, 2014)
Questions play an important role in every classroomboth students questions and teachers questions. The types of question used by teacher can help students to lift their own levels of understanding toward the concept given or even to build up new ideas. The study explored (1) how eventually teachers provide some ease to the students in creating an interactive classroom interaction through questions and answers exchanges; (2) how the questioning technique used by the teachers might encourage the students to be active in classroom interaction. By using Browns Interaction Analysis System (BIAS) the data were analyzed in order to find out what types of question were mostly used by the teachers during teaching learning process in encouraging the students activeness. The data were collected through observations in two English classes in SMP N 2 Pekalongan with two different English teachers. The data showed that the cognitive level of teachers questions which mostly occurred was lower order cognitive questions. The questions were aimed to invite the learners to speak and deliver their ideas. Based on the observed data, in details, the result showed that teachers used recall questions for 52%, comprehension for 42% and application occupied the remaining that was 6%. The target language was usually used on several occasions such as praising, encouraging, explaining and giving directions during the classroom interaction. Therefore, the suggestions are given to the teacher to understand practical uses of questioning techniques in minimizingstudents barriers to speak up in English.